Implementasi Penerapan Peraturan Daerah Kota Batam Nomor 2 Tahun 2011 tentang Bangunan Gedung terhadap Bangunan Gedung Perhotelan di Kota Batam - Noverina Syukura Linanda (Universitas Internasional Batam, 2019)
Development in Batam is developing very rapidly because Batam is a city located in Riau Islands Province. In reality, there are many regulation that related to the problem of development, so that there is less legal certainty in Building Permit or often short with IMB, There are more hotel building in Batam that violates because it does not have Building Permit or hotel that already has Building Permit but violates the Local Regulation of Batam City number 2 of 20b11 on Building in Batam. The Sociological Juridical Approach is directed to reality by looking at the application of the law (Das Sein), in this case the Local Regulation of Batam number 2 of 2011 on Building. Researchers choose this type of legal research because the researchers see the difference between the desired rule of law (Das Sollen) with the reality that happened (Das Sein) that occurred in Batam, it is not all that violate but there are still violations of hotel buildings regulations in Batam. Results of Research on Implementation that has not been run effectively, especially to the distance between hotel buildings that are not in accordance with the rules that have been applied. Lack of public awareness to follow the regulations has not been effective against the Local Regulation of Batam City number 2 of 2011 on Building.